The hygiene hypothesis: current perspectives and future therapies - Stiemsma LT; Reynolds LA; Turvey SE; Finlay BB (ImmunoTargets and Therapy, 2015)
Leah T Stiemsma,1,2 Lisa A Reynolds,3 Stuart E Turvey,1,2,4 B Brett Finlay1,3,5 1Department of Microbiology & Immunology, University of British Columbia, 2The Child and Family Research Institute, 3Michael Smith Laboratories, University of British Columbia, 4Department of Pediatrics, University of British Columbia, 5Department of Biochemistry and Molecular Biology, University of British Columbia, Vancouver, BC, Canada Abstract: Developed countries have experienced a steady increase in atopic disease and disorders of immune dysregulation since the 1980s. This increase parallels a decrease in infectious diseases within the same time period, while developing countries seem to exhibit the opposite effect, with less immune dysregulation and a higher prevalence of infectious disease. The “hygiene hypothesis”, proposed by Strachan in 1989, aimed to explain this peculiar generational rise in immune dysregulation. However, research over the past 10 years provides evidence connecting the commensal and symbiotic microbes (intestinal microbiota) and parasitic helminths with immune development, expanding the hygiene hypothesis into the “microflora” and “old friends” hypotheses, respectively. There is evidence that parasitic helminths and commensal microbial organisms co-evolved with the human immune system and that these organisms are vital in promoting normal immune development. Current research supports the potential for manipulation of the bacterial intestinal microbiota to treat and even prevent immune dysregulation in the form of atopic disease and other immune-mediated disorders (namely inflammatory bowel disease and type 1 diabetes). Both human and animal model research are crucial in understanding the mechanistic links between these intestinal microbes and helminth parasites, and the human immune system. Pro-, pre-, and synbiotic, as well as treatment with live helminth and excretory/secretory helminth product therapies, are all potential therapeutic options for the treatment and prevention of these diseases. In the future, therapeutics aimed at decreasing the prevalence of inflammatory bowel disease, type 1 diabetes, and atopic disorders will likely involve personalized microbiota and/or helminth treatments used early in life. Keywords: inflammatory bowel disease, microbiota, helminths, atopic disease, type 1 diabetes